Transformasi Pendidikan Melalui Eksplorasi Teknologi Pada Kegiatan Pengabdian Masyarakat Di Kampung Bremi Distrik Manokwari Utara-Kabupaten Manokwari - Yammes J. Batkunde; Irmawati Leppang; Joice Pangulimang (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Educational transformation through technological exploration in society changes the paradigm and has a significant impact on the way people learn. It is important to clearly understand the aspects contained in educational transformation in technological exploration. Various technological literacies, both through online learning, distance learning, This transformation not only brings opportunities, but also challenges that require cooperation, innovation, and interesting learning experiences. The importance of understanding the implications of digital transformation in the way people learn is emphasized to face rapid technological changes. With technological advances, many changes will be brought, information that arrives so quickly, learning by the community that is easy to do anywhere and anytime because in today's era, technology has lived side by side with society.